Development of Smart Cities in North Africa - V. K. Mitina (Контуры глобальных трансформаций: политика, экономика, право, 2023)
The article discusses the implementation of the “smart city” concept in the countries of North Africa. The purpose of the study is to find out how successfully the plans to create the cities of a new generation are implemented in the states of the region. Against the background of environmental problems, water and electricity shortages, rapid population growth and urbanization, as a result of which a number of slums are growing and there is a shortage of housing, «smart cities» are becoming extremely relevant for the countries of North Africa. In addition, the states of the region have good prerequisites and advantages for the implementation of such projects. For example, the lack of a rich background in many North African cities allows to introduce the most modern technologies, and there are also great opportunities for developing alternative energy, which is often used in the cities of a new generation. At the same time, when implementing the concept under consideration, the countries face a number of problems such as technological dependence on other states, lack of qualified personnel, failure to complete work on time. The development of smart cities is considered on the example of the analysis of relevant projects in the countries such as Algeria, Egypt, Morocco and Tunisia. As a result of the study, conclusions were drawn that without partnership with Western countries and China, the countries of North Africa cannot yet implement smart city projects. In addition, it is worth noting that in the region there is a correlation between the level of oil and gas reserves in the country and how much attention its government pays to the development of new generation city projects – the more reserves, the less “smart city” technologies are being introduced. It can also be assumed that by actively developing smart city projects from scratch, governments are moving away from solving problems in existing cities, which negatively affects their residents.